Pengaruh pH Terhadap Pembentukan Bintil Akar , Serapan Hara N, Pdan Produksi Tanaman pada Beberapa Varietas Kedelai pada Tanah Inseptisol Di Rumah Kasa - Danu Syahputra Lubis; Asmarlaili S. Hanafiah; Mariani Sembiring (Universitas Sumatera Utara, 2015)
Indonesia is an agrarian country which focuses on agriculture sector, but has a lot of acid reaction soil. Among all plant species for cultivation activity, soybean is one of the most often plant which use for cultivation activity in Indonesia. The Purpose of this research is finding the effect of pH on root nodule formation, nitrogen and phosphorusuptake and crop production on some varieties of soybean in Inceptisol at screen house. This research use randomized block design factorial method, with 2 factor, first was pH, second was soybean varieties which quantity and weight of root nodule, plant’s nitrogen and phosphorus content, plant’s nitrogen and phosphorus uptake, soil pH, dry plant weight, and also quantity of pod plant as the parameter. The result of this research show that Tanggamus was the variety which had quantity of pod most is about 108 and also the most high nitrogen content 3.218 % in both condition of pH.Keyword : Soil pH,Soybean, Root Nodule, Nitrogen, phosphorus